Hubungan Pengetahuan dan Sikap dengan Kejadian Hipertensi pada Lansia - Jessanta Kristina Telaumbanua; Delisman Waruwu; Raviatul Rahma; Maharani; Tiarnida Nababan (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Tanjungpinang, 2025)
Hypertension refers to elevated blood pressure that surpasses healthy thresholds, leading to issues with blood vessels. Factors such as knowledge, behaviors, and attitudes can influence thedevelopment offhypertension. The objective of this research is toexplore the connection betweennknowledge and attitudes regarding the prevalence offhypertension among older adults. This study employed a quantitative design utilizing the Analytical Survey method and a Cross Sectional framework focused on the UPT Lolofitumoi Health Center Area. The study's target population included all elderly individuals diagnosed with hypertension, totaling 290 participants, and a purposivessamplingttechnique waseemployed based on the Slovin formula, resulting in a sample size of 74 individuals. Data were gatheredusing a questionnaire, andbivariate analysis was performedthrough the chi square method. Findings revealed that a significant portion of participants demonstrated good knowledge, with 39 individuals (52.7%) exhibiting this trait, while 38 individuals (51.4%) maintained a positive attitude, and most of the hypertension cases were actually non-hypertensive, accounting for 42 individuals (56.8%). The analysis yielded chissquare results with a significantp-value of 0.004, indicating a correlation betweennknowledge and the incidence ofhypertension among theelderly.Additionally, a p-value of 0.003 suggested a connectionbetween attitudes and the occurrences of hypertension in this age group.